Florinetta and the Food of Freedom: Morgante XIX - Palma, Pina (Table talk. Perspectives on food in medieval Italian literature, 2010)
Keywords: dept.wll

Los Que Sobran = Those Not Spared - Barros, Pía (Asterión, 2010)
Keywords: 21st century; 21st century; Chilean fiction; Chilean fiction; Translations into English; Translations into English; Chilean fiction; Women authors; Women authors; Chilean fiction; dept.wll; faculty_collection

A Revolution of Shadows: Culture and Representation in Early-Twenieth-Century Mexico - Hernández Rodríguez, Rafael (The Popular Avant-Garde, 2010)
The avant-garde has been popular for some time, but its popularity has tended to fly under the radar. This “popular avant-garde,” conceived as the meeting ground of the avant-garde and popular, avoids the divorce of art and praxis of which the avant-garde has been accused. The Popular Avant-Garde takes stock of the debates about both the “historical” (“modernist”) and posterior avant-gardes, and sets them in relation to popular culture and art forms. With a critical introduction that examines the concepts of “the avant-garde,” “the popular,” and “the popular avant-garde,” the series of essays analyzes the way in which the avant-garde employs popular genres for political purposes, as well as how the popular acquires a critical function with respect to the avant-garde. Each of the volume’s three sections considers a different aspect of the productive exchange between the avant-garde and popular: the popular avant-garde as a culturally hybrid and cross-border phenomenon; the play between the popular avant-garde and developments in media and technology; and the popular avant-garde’s upending of conventional ideas about “the people” and “the popular.” The Popular Avant-Garde takes a fresh look at the now canonical Dadaist, Futurist, and Surrealist movements from the perspectives of gender and sexuality, and cultural and critical theory, while at the same time exploring less well-known avant-garde work in literature, film, television, music, photography, dance, sculpture, and the graphic arts. This volume’s coverage of the American and Afro-American, Luso-Brazilian and Latin-American, East-European, and Scandinavian avant-gardes, in addition to the vanguards of Spain and other parts of Western Europe, will appeal to all those interested in avant-garde and popular art forms.
Keywords: Avant-garde (Aesthetics); Popular culture; dept.wll; faculty_collection

Why did the monkey kill the giant? Another look at Margutte's death - Palma, P. (Quaderni d'Italianistica, 2010)
In the Morgante through Margutte's death-by-laughter Pulci voices a caustic critique of Ficino's philosophical theories while obliquely denouncing Lorenzo de Medici's acceptance of them. The spectacle of the monkey wearing and taking off Margutte's boots follows Aristotle's definition of the ridiculous that ignites hilarity. It also retrieves Bergson's idea of a society that can be derided because of its attempts to disguise its true self. Most importantly, it reintroduces Petrarch's concepts of similitudo and identitas. Through the depiction of the giant's death Pulci reveals the dignity of a poet remaining true to his poetic discourse even while coming to terms with the negative turn his career has taken.
0 citations (Crossref) [2023-10-31]
Keywords: dept.wll

Jews and Jewishness in Carme Riera‘s Dins el darrer blau - Sosa-Velasco, A.J. (Iberian Modalities: A Relational Approach to the Study of Culture in the Iberian Peninsula, 2010)
Las hogueras del fanatismo y la ortodoxia son una constante del siglo XXI, en el que ya estamos. Seguimos proyectando nuestro peor yo sobre los débiles, los pobres y los emigrantes. Necesitarí amos matar el yo racista que llevamos dentro y eso sólo se puede conseguir colocándonos en el lugar del otro, sintiéndote agredida. In the last twenty-five years, Jews have emerged as a literary figure as well as a literary theme in Spain. Catalan writers such as Maria Àngels Anglada (1930- 99), Carme Riera (1948–), and Vicenç Villatoro (1957–) approach the Jewish theme and the representation of the Jew as literary character in order to reflect on issues regarding identity and history in novels, such as El violí d‘Auschwitz (1994), Dins el darrer blau (1994), and Memòria del traïdor (1996), respectively. With Dins el darrer blau, written between 1989 and 1993, published in Catalan in 1994 and in Castilian in 1996, Riera starts a series of novels dedicated to the Majorcan xuetes (Jews who were converted to Christianity) which she finishes with Cap al cel obert in 1999. In this essay I will reflect on how Riera‘s Dins el darrer blau revisits the past in order to create a “culture of memory,” a process in which society confronts its traumatic past and the history of exile and repression, linking the history of the Jewish converts to the history of the Balearic island, Majorca. Riera‘s novel is based on historical events that occurred in the City of Majorca from 1687 to 1691. © 2013 Liverpool University Press.
Journal Abbreviation: Iber. Modalities: A Relat. Approach to the Study of Cult. in the Iber. Penins.
Keywords: dept.wll

Bilingualism and Learning - Verplaetse, L. S.; Schmitt, E. (International Encyclopedia of Education (Third Edition), 2010)
Bilingualism is defined as a speaker's ability to use two languages for communication. Due to the complexity of its nature, the study of bilingualism relies on several fields within linguistics, anthropology, psychology, neuroscience, and education. The study of bilingualism describes language behaviors of bilingual speakers, social and pragmatic patterns of using two languages, language development, and acquisition and loss, among other issues. Researchers attempt to explain the effect that bilingualism has on human cognition, societal relationships, and education of bilingual children. This article discusses bilingualism and learning from three perspectives: types of bilingualism, bilingual processing, and bilingualism and academic learning.
Citation Key Alias: lens.org/011-256-520-522-91X, pop00385
Keywords: Academic language; Additive bilingualism; Anomie; Balanced bilingualism; Bilingualism; Code switching; Diglossia; Immersion model; Maintenance bilingual (education); Semilingualism; Sequential bilingualism; Sheltered content (instruction); Simultaneous bilingualism; Societal bilingualism; Subtractive bilingualism; Transitional bilingual (education); dept.wll

When boundaries are crossed: Evaluating language attrition data from two perspectives - Schmitt, Elena (Bilingualism: Language and Cognition, 2010)
This study provides an account for a long-term selective loss of L1 (Russian) morpho-syntactic and content components in early immigrants to the US. The analysis of naturally occurring data is carried out from the perspective of two theoretical approaches - three models developed within language contact (Myers-Scotton 2002, 2005) and the Activation Threshold hypothesis as a component of a neurolinguistic approach to bilingualism (Paradis, 2004, 2007). The results show that the language contact approach is useful in identifying morpheme types that are most vulnerable to attrition. The second approach helps explain the differential rate of loss of content morphemes in a variety of topics and account for variability in the rate of attrition of late system morphemes through frequency factors. The study demonstrates that by crossing the boundaries of one theory, and one view of language researchers can achieve a stronger explanatory power and identify the common and complementary features that both models provide.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/038-866-199-464-167 tex.unique-id: [object Object]
Keywords: dept.wll

Brazil, lyric, and the americas by charles a. perrone - Rodriguez, R Hernandez (The Latin Americanist, 2010)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-140-755-253-967 tex.type: [object Object]
Keywords: dept.wll; peer-reviewed

Gender and the mexican revolution: yucatán women and the realities of patriarchy by stephanie j. smith - Rodriguez, R Hernandez (The Latin Americanist, 2010)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/032-418-738-075-703 tex.type: [object Object]
Keywords: dept.wll; peer-reviewed